The Role of Policy in Facilitating Adoption of Climate-Smart Agriculture in Uganda - Ampaire, Edidah L.; Happy, Providence; Asten, Piet J.A. van; Radeny, Maren A.O. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
This study aimed at understanding the influence of policy frameworks on climate change adaptation in Uganda. It combined literature review on existing natural resource management policies, focus group discussions with farming communities and interviews with key informants across various policy implementation levels. Findings reveal that even when farmers are exposed to appropriate adaptation practices, adoption is still constrained by limited enforcement of policies and regulations. Various reasons constrain enforcement; policies are formulated through top–down approaches, NGOs and local governments are minimally involved while local communities are largely excluded. There is either lack of or existence of non-functional implementation structures prescribed by the policies. Coupled with unclear roles among actors, weak links between different administration levels, limited human and financial resources and political interference, the ability of smallholders to adopt climate-smart agriculture (CSA) is thus constrained. Due to lack of knowledge of what the policies provide for, smallholders are not able to demand their rights. There is need for more focused follow-up research on specific issues raised in this report.